(untitled) (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2015)
Aim of this essay is to stress the importance of being maternal uncle and sister of Polyneices for the interpretation of Sophocles’ Antigone 523 (including a discussion on Greek philanthropia), 902-914, 921-928. Particular attention is devoted to the myths of the “mourning sisters”, to the historical examples, to the myrologia and paramythia of sister’s love for dead brother in the oral tradition of Mani, in order to demonstrate the originality of the Sophoclean solution. Questo lavoro si propone di enfatizzare l’importanza di essere zio materno e sorella di Polinice per l’interpretazione dei vv. 523 (con inclusa la discussione del concetto di philanthropia), 902-914, 921-928 dell’Antigone di Sofocle. Vengono individuati esempi di amore di sorella per il fratello defunto nel mito (mourning sisters), nella realtà storica, nei myrologia e paramythia del Mani, al fine di mettere in evidenza la novità dell’amor di sorella nella tragedia sofoclea.